UNA NUEVA TECNICA PARA LA COLORACION DE LOS FROTIS DE SANGRE O DE MEDULA ESTERNAL - GONZALEZ GUZMAN, IGNACIO (Instituto de Salubridad y Enfermedades Tropicales, CD MEXICO, DF, MEX, 1945)
The precollagenous fibers in the vescicular zones and lymphatic nodules in Hashimoto's disease are described The microscopic appearance is demonstrated in 2 figures
BOL INST ESTUD MED BIOL
Keywords: TECNICA, COLORACION, FROTIS, SANGRE, MEDULA, ESTERNAL; CIENCIAS MEDICAS; CIENCIAS CLINICAS; PATOLOGIA CLINICA